A modern conception of postcholecystectomy syndrome (based on the materials of the Advisory Board held on May 4, 2019 in Almaty, Kazakhstan) - A. V. Nersesov; D. A. Kaibullaeva; O. S. Vasnev; L. K. Tashenova; M. M. Sakhipov; G. T. Berestimov; G. A. Akhmetzhanova; O. T. Ibekenov; M. O. Doskhanov; N. M. Zhumazhanov; Zh. M. Balzhanov; B. A. Aitmoldin; et al. (Фармакоэкономика, 2020)
Gallstone disease is revealed in 10–20% of the population with a clear tendency to affect the younger population. In a clinically manifested course, cholecystectomy remains the treatment of choice. Symptoms and signs persist or even become more severe after gallbladder surgery in 10-15% of cases (“postcholecystectomy syndrome”). Postcholecystectomy syndrome includes heterogeneous disorders of liver, pancreas, duodenum, sphincter of Oddi, etc. that can be associated with errors or negative consequences of surgical intervention. Often, symptoms may persist because of previously unrecognized chronic diseases of neighboring organs. The spectrum of effective conservative measures is rather limited. The Advisory Board was held on May 4, 2019, in Almaty (Kazakhstan) to re-estimate the definitions and categories related to the issue of the postcholecystectomy syndrome and to develop the diagnostic and treatment algorithm for patients with the postcholecystectomy dysfunction of the sphincter of Oddi. The statements discussed by the interdisciplinary team of gastroenterologists and surgeons were addressed to general practitioners, therapists, gastroenterologists, and surgeons. The Advisory Board emphasized that organic and functional biliary diseases manifest mainly by biliary pain, main characteristics of which were defined in the Rome IV consensus based on the statistical analysis of a large pool of clinical data. For a more accurate bile duct system assessment and the exclusion of cholelithiasis, the examination algorithm was proposed, which included abdominal ultrasound investigation, endoscopic ultrasound investigation of the pancreatobiliary area, and magnetic resonance cholangiopancreatography. Diagnostic algorithm for differentiation of functional biliary disorders from organic gastrointestinal pathology was developed. Sphincter of Oddi dysfunction may be considered as a postcholecystectomy syndrome manifestation in 1.5-3% of cases. Apart from rational nutrition, conservative management of functional gastrointestinal diseases implies  pharmacological therapy. The efficacy of non-steroidal anti-inflammatory drugs, prokinetics, nitrates, antispasmodics, calcium channel antagonists, botulinum toxin, and hymecromone was demonstrated in previous studies. Papillosphincterotomy is not effective in relieving biliary pain in cases of the sphincter of Oddi dysfunction. The proposed algorithm for the management of patients with the postcholecystectomy syndrome was presented.